Microbial degradation of 1,3-dichlorobenzene. - de Bont, J A (1986)
A gram-negative, peritrichously flagellated rod, tentatively identified as an Alcaligenes sp., was isolated from a mixture of soil and water samples by using 1,3-dichlorobenzene as the sole carbon and energy source. During growth on 1,3-dichlorobenzene, almost stoichiometric amounts of chloride were released. Simultaneous adaptation studies, as well as enzyme studies, indicated that 1,3-dichlorobenzene was metabolized via 3,5-dichloro-cis-1,2-dihydroxycyclohexa-3,5-diene to 3,5-dichlorocatechol. Subsequently, the latter product was cleaved, yielding 2,4-dichloromuconate. No initial hydrolytic step yielding 3-chlorophenol was detected in this species.